Search for single top production via FCNC at LEP at root s=189-208 GeV - Abdallah, J; Abreu, R; Adam, W; Adzic, P; Albrecht, T; Alderweireld, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; et al. (2004)
A search for single top production (e+e -→tc̄) via flavour changing neutral currents (FCNC) was performed using the data taken by the DELPHI detector at LEP2. The data analyzed have been accumulated at center-of-mass energies ranging from 189 to 208 GeV. Limits at 95% confidence level were obtained on the anomalous coupling parameters κγ and κZ.